Study of Apoptotic Processes in Cells of Monocyte-Phagocyte System During Development of Adjuvant Arthritis Prior to and After Administration of Fetal Liver Cells - Goltsev, Anatoliy N.; Yampolskaya, Ekaterina E.; Ostankov, Maksim V.; Bondarovich, Nikolay A. (Problems of Cryobiology and Cryomedicine, 2014)
Rheumatoid arthritis (RA) is one of the most widespread chronic inflammatory diseases of the joints with multifactor etiology. A crucial point in RA is the disorder of proliferation and apoptosis in immunocompetent cells as well as in the cells of monocyte-phagocyte system (MPS). Using the model of adjuvant arthritis (AA) in animals we comparatively assessed the development of apoptotic processes in MPS cells before and after administration of native and cryopreserved fetal liver cells (cFLCs). By means of Western blot analysis we showed the peculiarities of CD-95 cascade proteins expression in MPS cells during development of AA. After administration of cFLCs we found more pronounced proapoptotic effect, which degree depended on the period of their administration. Probl Cryobiol Cryomed 2014; 24(3):249-261.